Global Governance, Democracy and Administrative Reforms in the Developing Countries - Dhakal, Mana Hari (Journal of Contemporary Review, 2024)
This article emphasis Democracy and reforms in developing countries. Due to the international development system, the countries of the world have been divided into 3 parts. Countries with a Human Development Index (HDI) of 0.116 to 0.489 are the third world, countries with low human development are the Second World, and countries with a HDI of 0.501 to 0.790 are the Developed Countries. This situation is seen when countries with a HDI of 0.800 to 0.996 are divided into three parts. The way the world order theory has been practiced is seen as a problem. When the world is divided into three parts, the most exploited country is the third world. Developed countries want to control the developing underdeveloped countries. Their civilization gives the name of good governance to developed politics, monopolizes the means of production, the distribution of goods, and takes advantage of their desires, as well as buying raw materials at a cheap price, processing them and selling them at a higher price, sending them to poor countries for research and testing drugs in the name of great assistance. By dividing the world into two parts, developed and developing countries, it has been tried to highlight the problems of developing countries, which are also plagued by poverty and political instability and corruption. There is a lack of efficiency in governance. The main crisis can be highlighted as follows: Developing and underdeveloped societies are in crisis in all respects. On the one hand, the possibility of cultural appropriation in the name of modernization has increased, while on the other hand, development has also affected internal resources and has Due to the international development system, the countries of the world have been divided into 3 parts. Countries with a Human Development Index (HDI) of 0.116 to 0.489 are the Third World, countries with low human development are the Second World, and countries with a HDI of 0.501 to 0.790 are the Developed Countries. This situation is seen when countries with a HDI of 0.800 to 0.996 are divided into three parts.